Comparisons of Performance Status, Pain, Nutrition Impact Symptoms, Sleep Quality, and Nutritional Status between Adult and Older Adult Patients with Head and Neck Cancer - Prasertsang, Areeya; Wirojratana, Virapun; Chayaput, Prangtip; Keskool, Phawin (Journal of The Royal Thai Army Nurses, 2021)
This research aimed to investigate the differences among performance status, pain, nutrition impact symptoms, sleep quality and nutritional status in 140 adult and older adult patients with head and neck cancer in a single tertiary hospital, Bangkok. A sample was enrolled regarding study criteria which comprised of 75 adults (53.6%) and 65 older adults (46.4%). The Roy Adaption Model was employed as a conceptual framework of study. Data were collected using the Palliative Performance Scale for Adult Suandok version, the Short-Form McGill Pain Questionnaire-Thai version, the Head and Neck Patient Symptom Checklist, the Pittsburgh Sleep Quality Index and the Mini-Nutritional Assessment-Short Form. Data analysis for comparing differences between groups was performed using Two Way ANOVA. The results reported that adult and older adult groups had average ages of 47.61 years (SD=9.09) and 70.58 years (SD=7.40). Most of them were males (77.3% and 72.3%, respectively). Concerning clinical data, tumor sites and histological findings differed significantly (χ2 = 19.108, p = .003 and χ2 = 19.512, p = .001, respectively). Comparative analyses after controlling tumor sites and histological findings revealed no differences among performance status, pain, nutritional impact symptoms, sleep quality and nutritional status between adult and older adult groups (p>.05). In conclusion, even though, selected study factors demonstrated some alterations regarding adaptation, no statistical differences found between two age groups.